Governing the toxics and the pollutants. France, Great Britain, 1750–1850. Issue 2 (June 2016) - Le Roux, Thomas
Highlights: Sciences and politics at the time of industrialization. Chemistry as art of governance. Toxics, pollutants and discourses of justification. Transforming the law and commodifying the environment.